Smart Fertilizers —A boon for Indian agriculture - Jaga, Praveen K; Garg, V K (Indian Farming, 2022)
In Indian agriculture, there is a lot of technological development taking place. Despite availability of smart fertilizers, their use in agriculture is very limited i.e. less than 1% of the total worldwide fertilizer consumption. Several advantages could be observed in smart fertilizer compared to conventional fertilizer. Smart fertilizers based on slow or controlledrelease and carrier delivery system have been shown to improve crop yields, soil productivity and lower nutrient loss compared to conventional fertilizers. Seven materials like clays, monoclays, polymers and harvesting residues are suitable for the development of smart fertilizers by acting as carrier matrices for nutrients and bacterial inoculants. Smart fertilizers would reduce losses of nutrients, prolong fertilizer cycles and enhance effective nutrient uptake by crops. These can substantially decrease the risk of environment pollution. Taking into account these economic aspects and the extremely important environmental aspect, the use of smart fertilizers in Indian agriculture would benefit farmers. Smart fertilizer could be boon for Indian agriculture.